Україна у двох світових війнах: воєнна історія й антропологія - Лисенко, О. (Інститут історії України НАН України, 2008)
In the article the attempt of comparative analysis of І and ІІ world wars is made through the prism of military history and anthropology. The specific moments of functioning of different social groups of Ukrainian society (military servicemen, prisoners of war, civil population) is exposed in the existential terms of wartime. The behavioural models of stable and temporal social conglomerates and survival strategies are reconstructed on group and individual levels.